"An efficient higher order non-polynomial quasi 3-D theory for dynamic responses of laminated composite plates" [Composite Structures 189 (2018) 386–397]. (15th October 2021) - Zenkour, Ashraf M.
Abstract: This comment paper aims to show that the paper (Adhikari and Singh [1]) contains a serious error. In the commented paper, the displacements are incorrect—two of the shape functions they are based on are erroneous, and they do not properly account for the same degree. The correct forms of the shape functions are explained more deeply here.